1992
DOI: 10.1002/ajh.2830410306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium permeabilization and membrane‐attached hemoglobin on erythrocyte deformability

Abstract: The present study was designed to evaluate the influence of intracellular calcium [Ca]i regulated membrane attached hemoglobin (Hbm) on the deformability of human RBC and ghosts. [Ca]i of RBC was elevated via the ionophore A23187 (10 microM); the deformability of RBC and resealed ghosts was determined via measuring RBC and ghost transit times through 5 microns diameter pores with the Cell Transit Analyzer (CTA). Salient results included: (1) significantly increased RBC levels of Hbm following ionophore treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…It is accepted now that RyR channels are activated by Ca 2 + at nanomolar level and inhibited by Ca 2 + at micromolar level (Lai et al, 1988;Bull and Marengo, 1993;Wayne Chen et al, 1997;Sonnleitner et al, 1998;Friederichs et al, 2006). Several groups reported that the activity of RyR1 could be almost entirely inhibited as [Ca 2 + ] ex concentration rises to 1 mM (Bull and Marengo, 1993;Yin et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is accepted now that RyR channels are activated by Ca 2 + at nanomolar level and inhibited by Ca 2 + at micromolar level (Lai et al, 1988;Bull and Marengo, 1993;Wayne Chen et al, 1997;Sonnleitner et al, 1998;Friederichs et al, 2006). Several groups reported that the activity of RyR1 could be almost entirely inhibited as [Ca 2 + ] ex concentration rises to 1 mM (Bull and Marengo, 1993;Yin et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…The lipid peroxidation, proteins cross-linking and the attachment of hemoglobins increase the membrane viscoelasticity. Evidence shows that [Ca 2 + ] in increase also causes the perturbations of membrane skeletal protein network (Friederichs et al, 2006), which would give rise to membrane instability and lead to the loss of cell surface area and then the deformability, and even cell lysis (Zail, 1986;Kalfa et al, 2006). It was also reported that [Ca 2 + ] in could affect the elastic modulus and RBC deformability through changing the transmembrane potential (Trayko and Rakesh, 1986).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although hemoglobin binding to other hemoglobin subunits depends on Fe 2ϩ and O 2 , it is not known to bind calcium; however, hemoglobin can bind to reticulocyte membranes in the presence of calcium (32), suggesting that it may be a partner for some other calcium binding membrane-bound protein. Similarly, it is possible that citrate synthase and carbonic anhydrase can associate with some other as yet uncharacterized protein in the presence of calcium.…”
Section: Resultsmentioning
confidence: 99%